Controlling heater for a portable egg incubator - Zainuddin, Aznilinda (2004)
This thesis describes the design of temperature controller of a home egg incubator. This project intends to build a system that regulates the temperature in the incubator appropriate to fowls' egg incubation process using the micro controller Peripheral Interface Controller (PIC) as the main controller. The controller will enable the regulations of suitable temperature for at least 5 types of fowls such as chicken, turkey, duck, goose, and pigeon. The incubation is to hold about 30 eggs. The temperature is controlled by the PIC dependent on the occurrence of day and hour signals from the clock of the system. The PIC generates control for temperature egg incubation. The program for the PIC is written in assembly language and then downloaded into the micro controller to operate the circuit which is built to handle the electronics of heating and temperature sensing of the incubation chamber.